Clinical study on the influence of tea drinking habits on bone mineral density and osteoporosis in postmenopausal women in Fuzhou city, China - Li, Jian-Yang; Ge, Ji-Rong; Chen, Juan; Ye, Yun-Jin; Xie, Li-Hua; Li, Li; Chai, Hao (Progress in Nutrition, 2021)
Objective: To analyze the influence of tea drinking habits on bone mineral density (BMD) and osteoporosis (OP) in Chinese postmenopausal women in Fuzhou city after adjusting for the effects of confounding factors such as age, living habits, and diseases. Methods: 1134 cases of postmenopausal women living in Fuzhou city were randomly investigated, among which 947 cases met the requirements. There were 502 cases in the non-tea-drinking group, 326 cases in the occasional-tea-drinking group, and 119 cases in the daily-tea-drinking group. Researchers surveyed subjects’ age, menopause age, living habits, disease, and other factors. Body mass index (BMI) was calculated based on height and weight. BMD in the lumbar spine and hip was measured by dual-energy X-ray (DXA) absorptiometry. Results: Among the 947 postmenopausal women, 53.1% were non-tea-drinkers, 34.42% were occasional tea-drinkers, and 12.57% were daily-tea drinkers. The lumbar spine BMD of the daily-tea-drinking group was (0.788±0.115) kg / cm2, which was higher than the non-tea-drinking group of (0.737±0.106) kg / cm2 (p <0.001), The total femur BMD of the daily tea-drinking was (0.754±0.105) kg / cm2 higher than the non-tea-drinking group’s (0.737±0.106)kg / cm2, and the difference is statistically significant (p <0.001); The results of multiple linear regression analysis showed that daily tea-drinking was positively correlated with the BMD of the lumbar spine and total femur. The results of multivariate logistic regression analysis showed that drinking tea daily was an independent protective factor for osteoporosis. Conclusion: Drinking tea daily helps Chinese postmenopausal women maintain BMD in the lumbar spine and the total femur, and it could be an independent protective factor for osteoporosis. Keywords: Tea drinking habits, Postmenopausal women, Bone mineral density